A Prospect Theory of Power Transition: Why Power Transition Does Not Imply War? - WANG, Huan (Institutional Knowledge at Singapore Management University, 2015)
We present a prospect theory model to explain why power transitions do not necessarily lead to war. We ﬁnd that three major mechanisms prevent the occurrence of potential power transition wars. First, the dual boiling frog eﬀects occurring in the middle range of capability catching-up rate prevent a dominant state from preempting and a rising state from challenging the other side. Second, divergent expectations for favorable comparative growth advantage motivate both parties to keep the status quo. Third, the concerns of relative advantage deterioration over a third party in the post-war power structure help deter both parties from starting a war.